Pengaruh Celebrity Endorser Iklan Televisi Dan Kualitas Produk Terhadap Keputusan Pembelian Kosmetik Mustika Ratu Di Muara Enim - Arubina Bangsawan; Muhammad Deni; Nanda Revita; Marita Pratisila; Rialita Putri Elba (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to determine how the influence of Celebrity Endorser Television Advertising and Product Quality on the Purchase Decision of Mustika Ratu Cosmetics in Muara Enim. The research used purposive random sampling method. Thus, the number of samples in this study were 137 female respondents in Muara Enim district. The method of data analysis using the Multiple Linear Regression method. The results showed that Celebrity Endorser Television Advertising and Product Quality Influenced Purchase Decisions for Mustika Ratu Cosmetics in Muara Enim and the variable Celebrity Endorser Television Advertising was the most dominant variable influencing consumer purchasing decisions for Mustika Ratu cosmetics in Muara Enim district.